Investigating the Effect of Intramuscular Dexamethas on Duration of Labor in Post Date Pregnancy - L Hajivandi; S Montazeri; M Irvani; A Oliyai; MH Haghighi zade (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2013)
Introduction: One of the problems in midwifery is labor induction in the cases which the termination of pregnancy is necessary. Thus, the methods for cervical ripening and labor induction have always been taken into consideration. The aim of this study was to determine the effect of intramuscular dexamethasone on onset of labor in postdate pregnancy. Methods: This single-blind, randomized clinical trial study was performed on 100 nulliparous women who referred to Amir Al Momenin hospital in Ahvaz. The patients were randomly divided into two groups. Single dose of intramuscular dexamethasone (8 mg) was administered to the study group 12 h before induction. The controls were given 2 cc of normal saline at the same interval. Results: There was no significant difference between the two groups in terms of age, demographic characteristics, initial Bishop score, first and fifth minute Apgar score, and meconium. After the injection, Bishop score in the study group was 7/23 ± 1/32 and in the control group, it was 2/98 ± 0/89. Thus, the difference was significant (P<0.0001). The mean interval between induction with the onset of the active phase was 3/1±0.68 hours in the study group, whereas in the control group 4/2±1/3 hours was observed (P=0.001). Conclusion: The results of this study showed that intramuscular dexamethasone by improving Bishop score causes the onset of labor pains resulting in decrease of labor duration in postdate pregnancies.